(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study examines the contemporary psychological foundations for shaping patriotism among university students. Its purpose is to identify effective mechanisms that strengthen the patriotic motivations of young people in higher-education settings, drawing on the latest theoretical approaches and applied technologies in psychology. The research object comprised 18- to 24-year-old students enrolled in universities and institutes, while the research subject focused on their individual socio-psychological characteristics and patriotism-related motives. A mixed-method design was employed: quantitative tools (psychological diagnostic tests) were combined with qualitative methods (semi-structured interviews, focus-group discussions) and an experimental training program. Findings indicate that students with higher self-awareness, well-developed metacognitive skills, and strong socio-emotional competencies score significantly higher on patriotism measures (p < .01). In addition, short-term psycho-pedagogical interventions grounded in interest-based tasks and social-identification components raised patriotism indices by 15–18 percent. On the basis of these results, a psychological training module and a package of recommendations-both suitable for integration into higher-education curricula-were developed. The module is designed to nurture national pride, civic responsibility, and an active social stance in students.